2018
DOI: 10.1111/jgs.15285
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity in Older Adults in an Integrated Health Care System

Abstract: Food insecurity is prevalent even in older adults with private-sector healthcare coverage. Specific individual characteristics, and a model based on those characteristics, can identify older adults at higher risk of food insecurity. System-level interventions will be necessary to connect older adults with community-based food resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 34 publications
1
47
1
1
Order By: Relevance
“…Four studies (n = 51,541) ( Fig. 4) provided sufficient data to calculate an odds ratio of 2.41 [95% CI 1.81-3.22, Q(df = 3) = 8, I 2 = 63%], 39,52,77,82 while three (n = 825) ( Fig. 5) yielded a Hedges' g = 0.50 [95% CI 0.34-0.66, Q(df = 2) = 1.2, I 2 = 0%].…”
Section: Results Of Individual Studies and Synthesis Of Resultsmentioning
confidence: 99%
“…Four studies (n = 51,541) ( Fig. 4) provided sufficient data to calculate an odds ratio of 2.41 [95% CI 1.81-3.22, Q(df = 3) = 8, I 2 = 63%], 39,52,77,82 while three (n = 825) ( Fig. 5) yielded a Hedges' g = 0.50 [95% CI 0.34-0.66, Q(df = 2) = 1.2, I 2 = 0%].…”
Section: Results Of Individual Studies and Synthesis Of Resultsmentioning
confidence: 99%
“…In the US, the prevalence of adult food insecurity inside the health care setting has been reported to range between 13.2-19.1% [12,13,36]; however, one possible explanation for the observed among-country difference lays to the fact that in Greece, health care provision is provided to all for free, whereas in the US only insured individuals make use of the health care resources. In parallel, even in the US, research in the private health care setting has revealed a much lower prevalence of food insecurity compared with the public sector [37]. Nevertheless, despite the importance of the issue, research on the prevalence of food insecurity within the healthcare setting appears limited and conducted mainly in the US.…”
Section: Discussionmentioning
confidence: 99%
“…Two limitations with regards to our assessment of food insecurity deserve mention. First, we assessed food insecurity using a single question whose validity has not been determined (22,32), and which does not assess other related concepts (nutrition insecurity, undernutrition, hunger) which may be relevant in diabetes (36). Our food insecurity question was drawn from the Nutrition Health Screener of the Nutrition Screening Initiative, a validated instrument to assess nutrition in older adults (22).…”
Section: Discussionmentioning
confidence: 99%
“…Our food insecurity question was drawn from the Nutrition Health Screener of the Nutrition Screening Initiative, a validated instrument to assess nutrition in older adults (22). Previous work has shown that this item correlates well with known predictors of food insecurity (32). In a survey of 110 individuals with positive responses to the food insecurity question on the MTHA, 74% responded "sometimes" or "often" to one or both of the 2 questions in the Hunger Vital Sign (ref) (37,38).…”
Section: Discussionmentioning
confidence: 99%